Ensuring safety and feasibility for resection of pediatric benign ovarian tumors by single-port robot-assisted laparoscopic surgery using the da Vinci Xi system - Xu, Deqiang; Gao, Heyun; Yu, Shanzhen; Huang, Guangbin; Lu, Dan; Yang, Kun; Zhang, Wei; Zhang, Wen (Frontiers in Surgery, 2022)
Background: Single-port robot-assisted laparoscopic surgery (S-RALS) is rarely applied in pediatric surgery. There is still no study about the application of S-RALS for resection of pediatric benign ovarian tumors. The current study aimed to investigate the safety and feasibility of S-RALS for resection of pediatric benign ovarian tumors using Da Vinci Xi system. Methods: The clinical data of 3 patients who underwent S-RALS for resection of benign ovarian tumors in Department of Pediatric Surgery, Zhongnan Hospital of Wuhan University from May 2020 to September 2021 were retrospectively analyzed. The mean age of these children was 7.9 years (5.8-9.3 years). One was a case of bilateral ovarian tumors and the other two were cases of right ovarian tumors. Results: All the 3 patients successfully underwent the resection of ovarian tumors through S-RALS without conversion to laparotomy. The average operation time was 180 min (118-231 min). The average amount of blood loss was 20 ml (10-35 ml). No drainage tube was placed. All the postoperative pathological types of the ovarian tumors were mature cystic teratomas in the 3 cases. All the patients started a liquid diet 2 hours after surgery. The average length of postoperative hospital stay was 4.7 days (3-7 days). No tumor recurred and no surgical site hernia occurred, the wound healed very well with a cosmetic scar in the lower umbilical crease during the postoperative follow-up for 6-18months. Conclusion: S-RALS has the advantages of less surgical trauma, quick postoperative recovery and a cosmetic scar in the lower umbilical crease. It is safe, effective and feasible for pediatric benign ovarian tumors.